A new species of the Rhinella margaritifera (Laurenti 1768) species group (Anura, Bufonidae) from southern Brazilian Amazonia - Ávila, Robson Waldemar; Morais, Drausio Honorio; Perez, Renata; Pansonato, André; de Carvalho, Vinicius Tadeu; Rojas, Rommel R.; Gordo, Marcelo; Farias, Izeni Pires (Zootaxa, 2020)
Neotropical toads from the Rhinella margaritifera species group have been considered a taxonomic puzzle for a long time. Because of the high morphological similarity and an unknown number of undescribed taxa among the species of this group, we did an extensive search for character distribution within all nominal taxa. Herein we describe Rhinella parecis sp. nov. a new species from Southern Brazilian Amazon. We provide a morphological diagnosis, morphometric comparisons with similar species, and a molecular phylogenetic hypothesis on the relationships of the new species. Rhinella parecis sp. nov. is assigned to the R. margaritifera group and differs from others species by snout-vent length ranging 40.7–53.5 mm in males (n=12) and 44.9–54.8 mm in females (n=4), snout rounded in dorsal view, acute with fleshy ridge extending to tip of snout in lateral view, canthal and pre-orbital crests absent, supra-orbital, parietal and supra-tympanic crests present and low, dorsolateral row of tubercles present, bony protrusion at the angle of jaws absent, tympanum evident, vertebral apophyses absent and toes half-webbed. The new species is the 20th species associated to the R. margaritifera group distributed in the Chapada dos Parecis, a probable center of endemism in states of Rondônia and Mato Grosso, Brazil.